The Role of Brand Image, Food Safety, Awareness, Certification on Halal Food Purchase Intention: An Empirical Study on Indonesian Consumers - Purwanto, Agus; Haque, Marissa Grace; Sunarsi, Denok; Asbari, Masduki (AGUSPATI Research Institute, 2021)
The purpose of this study was to determine the factors that influence customer interest in buying halal processed food. We use the voluntary sampling method with 110 respondents who are halal food customers in Indonesia. The data analysis was performed using the SEM-PLS method. The research was conducted for one month by distributing questionnaires directly to respondents. This study to analyze brand image, perceived quality, perceived value, halal certification, health, halal awareness, and halal marketing as factors that influence customers' halal purchase intentions. The results showed that halal awareness, brand image, halal certification, health reasons, and perceived value have a positive and significant effect on purchase intention.